Assessment of Surface Water quality in Highly Urbanized Areas: A Case Study of the Vladayska River in Sofia - Radeva, Kalina; Marcheva, Zvezdelina; Matev, Simeon; Tamburadzhiev, Ilia (Geographica Pannonica, 2025)
This study investigates the impact of Sofia's urban areas on the physicochemical parameters of water quality along the Vladayska River. Two sections of the river were analyzed: (1) an upper, relatively unpolluted section from the source to the Vladaya district, used as a reference due to limited data availability, and (2) a lower section (Kubratovo), downstream of Sofia, influenced by anthropogenic activities. Based on the results, significant changes in the physicochemical parameters were observed in the lower section. Principal component analysis (PCA) was conducted on data for 15 water quality indicators, precipitation, and river runoff under different hydrological conditions (high flow, low flow, and winter season) for the lower section (Kubratovo). The PCA results identified nutrient and organic matter pollution and mineral content as key drivers of water quality variability. Additionally, hydrological factors were found to indirectly influence water quality in the downstream section at Kubratovo. As revealed by the CCME WQI index, the Vladayska River's upper section also experienced poor water quality between 2013 and 2015, improving to good in 2016–2018, likely due to reduced pollution from tourism and residential sources. In contrast, the downstream section at Kubratovo consistently exhibited poor water quality from 2010 to 2021, reflecting ongoing urban pollution with no observed trend of improvement.
Keywords: water pollution; urban river; PCA; water quality index; Bulgaria